Research on the Development Strategy of Commercial Bank Business Based on BCG Matrix: —Taking Bank A as an Example - Gao, Chengzhong (Asia Pacific Economic and Management Review, 2025)
Based on public annual reports and financial statistics from the People’s Bank of China, this study employs an adjusted BCG Matrix analysis to conduct an in-depth analysis of the main business operations of Bank A. The study finds that its business mainly falls within high-growth, low-market-share categories, lacking significant competitive advantages, with issues like insufficient market competitiveness, challenges in risk management, and ineffective policy implementation. Recommendations include enhancing market competitiveness by innovating financial products and personalized services, optimizing the customer relationship management system, and mitigating price disadvantages through market segmentation; strengthening risk management by introducing advanced risk management tools, optimizing business structure allocation, establishing risk mitigation mechanisms, and enhancing the risk management committee’s structure and team expertise; optimizing policy execution by adjusting internal incentive mechanisms, improving performance assessments for policy-related businesses, conducting regular internal training, and developing internal promotional materials, while also refining loan distribution channels to enhance cooperation with small and micro enterprises and individual business owners.